Peran Kader Kesehatan dalam Peningkatan Kesehatan Ibu Hamil selama Pandemi Covid-19: Literatur Review - Nugraha, Andhika Robbi; Yulian, Vinami (Prosiding Seminar Nasional Keperawatan Universitas Muhammadiyah Surakarta, 2023)
The COVID-19 pandemic has placed many restrictions on almost all health services. This greatly inhibits pregnant women to check the condition of their pregnancy. One of the roles played by cadres in assisting the implementation of health services for pregnant women is by motivating pregnant women and their families to want to attend classes for pregnant women. The purpose of the traditional literature review is to identify previous research related to the role of health cadres in providing health services for pregnant women during the Covid-19 pandemic. The method in this review is a literature search obtained from the Research Gate journal database, Springer Link, Pubmed, Science Direct, Google Scholar. The results of the researchers can conclude that health cadres have a very important role to keep monitoring and motivating pregnant women to carry out pregnancy checks to midwives regularly.